Structure–Property Relationship of Cyano‐Functionalized Conjugated Polymers for Photocatalytic Hydrogen Production. Issue 2 (9th November 2022) - Chi, Xu; Chen, Qian; Lan, Zhi‐An; Zhang, Xirui; Chen, Xiong; Wang, Xinchen
Abstract: Conjugated polymers (CPs) have garnered increasing attention in the field of photocatalysis due to their stability and molecular tunability. Understanding the structure–property relationship in CPs and addressing appropriate molecular design strategies are pivotal to improving the photocatalytic performance of CPs. Herein, a new efficient cyano (CN) engineering approach was proposed to promote the photocatalytic performance of CPs, and three representative CP‐based photocatalysts with different CN contents were tailor‐made to investigate the relationship between CN functionalization and photocatalytic activity. A series of systematically experimental and theoretical studies reveal that CN functionalization contributes to strengthening the donor‐acceptor (D‐A) interaction, enhancing the light absorption ability, charge separation/transfer efficiency, and hydrophilicity of CPs, and also facilitating the output of separated photoinduced electrons from CPs to Pt cocatalyst. Thus, the dicyano‐functionalized polymer (P‐2CN) manifests an attractive photocatalytic performance in hydrogen production. This study provides a facile strategy to develop excellent CP‐based photocatalysts for solar fuel production. Abstract : Photocatalysis : The increase in the degree of CN functionalization can regulate the D‐A interaction with beneficial effects, such as broadened light absorption range, improved charge separation, enhanced interaction with Pt cocatalyst, and strengthened hydrophilicity, which achieves an excellent activity in the photocatalytic hydrogen production reaction.